Meis1 programs transcription of FLT3 and cancer stem cell character, using a mechanism that requires interaction with Pbx and a novel function of the Meis1 C-terminus - Wang, Gang G. (© 2005 by The American Society of Hematology, 2005)
Meis1 is a homeodomain transcription factor coexpressed with Hoxa9 in most human acute myeloid leukemias (AMLs). In mouse models of leukemia produced by Hoxa9, Meis1 accelerates leukemogenesis. Because Hoxa9 immortalizes myeloid progenitors in the absence of Meis1 expression, the contribution of Meis1 toward leukemia remains unclear. Here, we describe a cultured progenitor model in which Meis1 programs leukemogenicity. Progenitors immortalized by Hoxa9 in culture are myeloid-lineage restricted and only infrequently caused leukemia after more than 250 days. Coexpressed Meis1 programmed rapid AML-initiating character, maintained multipotent progenitor potential, and induced expression of genes associated with short-term hematopoietic stem cells (HSCs), such as FLT3 and CD34, whose expression also characterizes the leukemia-initiating stem cells of human AML. Meis1 leukemogenesis functions required binding to Pbx, binding to DNA, and a conserved function of its C-terminal tail. We hypothesize that Meis1 is required for the homing and survival of leukemic progenitors within their hematopoietic niches, functions mediated by HSC-specific genes such as CD34 and Fms-like tyrosine kinase 3 (FLT3), respectively. This is the first example of a transcription factor oncoprotein (Meis1) that establishes expression of a tyrosine kinase oncoprotein (FLT3), and explains their coexpression in human leukemia. This cultured progenitor model will be useful to define the genetic basis of leukemogenesis involving Hoxa9 and Meis1.